Unraveling Data’s Gordian Knot : Enablers and Safeguards for Trusted Data Sharing in the New Economy - World Bank (World Bank, Washington, DC, 2021)
As countries around the world battle the Coronavirus (COVID-19) pandemic, the importance of sharing and using data effectively has never been more apparent. Data collection and analysis tools for diagnostics, detection, and prediction are of critical importance to respond intelligently to this crisis and prevent more lives from being lost. An effective response requires data to be shared between institutions, across sectors, and beyond national borders. Because data is critical to understanding, anticipating, and responding to the crisis, new approaches to share data are being tried, some which may have concerning consequences for individual data protection. It is an extraordinary moment where the use of personal data for helping society may potentially come into conflict with data protection norms. The aim of this report is to highlight emerging practices and interesting features of countries’ current approaches to establishing these safeguards and enablers of data sharing.